The Effect of Profitability, Corporate Governance, Inventory Intensity on Tax Avoidance (in Mining Companies listed on the Indonesia Stock Exchange for the period 2017-2021) - Natalina (GoAcademica Research & Publishing, 2023)
The larger the profit, the greater the amount of income tax that will need to be payed. Meanwhile, taxes are sometimes viewed as a